De coeficientes enteros con uso de parentesis:

2...15x – 10 = 6x – (x + 2) + (-x + 3)
4....30x – (-x + 6) + (-5x + 4) = -(5x + 6) + (-8 + 3x)
6.....3x + [-5x – (x + 3)] = 8x + (-5x – 9)
8......x – [5 + 3x – {5x – (6 + x)}] = -3
10....71 + [-5x + (-2x + 3) = 25 – [-(3x + 4) – (4x + 3)]

Por favor rapido


1

Respuestas

2012-07-18T01:10:23+02:00

2..

15x – 10 = 6x – (x + 2) + (-x + 3)
15x - 10 = 6x - x - 2 - x + 3
15x - 10 = 4x +1
15x - 4x = 1 + 10
       11x = 11
          x = 11/11
          x = 1

 

4..
30x – (-x + 6) + (-5x + 4) = -(5x + 6) + (-8 + 3x)
        30x + x - 6 - 5x + 4 = - 5x - 6 - 8 + 3x
                          26x - 2 = - 2x - 14
                       26x + 2x = - 14 + 2
                               28x = -12
                                  x = -12/28
                                  x = - 3/7

 

6..
3x + [-5x – (x + 3)] = 8x + (-5x – 9)
3x + [-5x - x - 3 ] = 8x - 5x - 9
3x + [ -6x -3 ] = 3x - 9
3x - 6x - 3 = 3x - 9
     - 3x - 3 = 3x - 9
      -3 + 9 = 3x + 3x
             6 = 6x
          6/6 = x
            1 = x

 

8..
x – [5 + 3x – {5x – (6 + x)}] = -3
x - [ 5 + 3x - {5x - 6 - x}] = -3
x - [ 5 + 3x - {4x -6}] = -3
x - [ 5 + 3x - 4x + 6 ] = -3
x - 5 - 3x + 4x - 6 = -3
                      2x = -3+5+6
                      2x = 8
                        x = 8/2
                        x = 4

 

10..
71 + [- 5x + (-2x + 3)] = 25 – [-(3x + 4) – (4x + 3)]
71 + [ - 5x - 2x + 3] = 25 - [ - 3x - 4 - 4x - 3]
71 + [ - 7x +3 ] = 25 - [ - 7x - 7 ]
71 - 7x + 3 = 25 + 7x + 7
      74 - 7x = 32 + 7x
      74 - 32 = 7x + 7x
            42 = 14x
              x = 14/42=2/6
               x= 1/3

 

*Espero haberte ayudado, saludos.